OS 29-06 RESPONSE TO HEMORRHAGE FOLLOWING CATHETER-BASED RENAL DENERVATION IN SHEEP WITH HYPERTENSIVE KIDNEY DISEASE. (September 2016) - Denton, Kate; Moritz, Karen; Booth, Lindsey; May, Clive; Head, Geoff; Schlaich, Markus; Singh, Reetu
Abstract : Objective: Renal sympathetic nerves contribute significantly to the control of kidney function and blood pressure. A critical question is whether catheter-based renal denervation (cDNX) has adverse consequences, in situations of clinical challenge, such as hemorrhage. The aim was to examine the effects of cDNX on basal mean arterial pressure (MAP) and glomerular filtration rate (GFR) and in response to hemorrhage in hypertensive sheep with chronic kidney disease (CKD). Design and Method: Hypertension and CKD was induced in sheep by performing fetal unilateral nephrectomy (CKD; N = 14). Sham surgery was also performed (Control; N = 14). At 6 months of age, MAP, GFR and plasma renin activity (PRA) was measured and at 10 months, either cDNX (CKD-cDNX; N = 7, cDNX; N = 7) or sham procedure was performed (CKD-Intact; N = 7, Control-Intact; N = 7). At 2 months post-cDNX, MAP and GFR, before, during and after hemorrhage (20% blood volume withdrawn over 15 minutes) was assessed. Results: At 6 months of age, CKD sheep had significantly higher MAP (6mmHg) and lower GFR (30%) than control. At 2 months post-cDNX, MAP in CKD-RDN sheep fell to levels similar to control sheep without any effect on GFR. In response to hemorrhage, the greatest decrease in MAP occurred in the CKD-RDN group. In the Control-Intact sheep this fall in MAP gradually recovered, associated with an increase in PRA. In contrast in the Control-RDN and CKD-RDN group, PRA did not increase and the MAP did not recover. Conclusions: cDNX effectively reduced blood pressure 2 months following cDNX in previously hypertensive sheep but had no effect on GFR. However, the lack of reflex activation of neural mechanisms may impair a patient's ability to adequately respond to physiological challenges to extracellular homeostasis.